The Evolution of 'Kafir' in the Qur’an: A Diachronic Study on the Socio-Political Influences Shaping Its Meaning - Muawwanah, Nafisatul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
The term 'kafir' in the Qur’an possesses a complex meaning, which is one of the most pivotal elements of the Qur’an, influenced by the context from the time of revelation to the practice of the interpretive community. Considering the element of time, the meaning of 'kafir' has changed over the years; it is dynamic and dependent on temporal, spatial, and socio-political contexts. This paper explores the historical-critical changes in the meaning of 'kafir' over time, known as a diachronic study, by considering the socio-political backgrounds accompanying these emerging meanings. The objective of this paper is to foster a more comprehensive understanding of 'kafir' as a dynamic and discursive term throughout history. The findings indicate that with the continuous evolution of context, different understandings and meanings have surfaced, rendering the meaning of 'kafir' fluid. The term dates back to pre-Islamic times and was later used in the Qur’an within a new conceptual framework. Within the interpretive community, political divisions in the first centuries of Islam contributed to diverse meanings of 'kafir.' In the modern era, the predominance of the nation-state concept has brought the term 'kafir' into debates concerning the relationship between Muslims and non-Muslims and their status within the nation-state. This type of historically grounded diachronic study helps to avoid essentialism in the study of historically significant terms and concepts related to Muslim societies, which are still often examined in popular academic discourse.